Decellularized Matrix Scaffolds for Vascular Transplantation: Addressing Immunogenicity, Sterilization, and Current Strategies for Long-Term Storage - Shevchenko, Yevhen V.; Liadova, Tetiana I.; Hladkykh, Fedir V.; Matvieienko, Mariia S.; Chyzh, Mykola O.; Komorovsky, Roman R. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Cardiovascular diseases are the leading cause of death globally, with their incidence rising rapidly. For obstructive cardiovascular diseases, definitive treatment options include surgical interventions such as vascular stenting, replacement surgery, or vascular bypass. Decellularized extracellular matrix scaffolds, designed through tissue engineering, hold great potential in addressing the donor shortage issue. The aim. To conduct a comparative analysis of sterilization methods for decellularized matrix scaffolds used in vascular transplantation, based on information from open sources. Materials and methods. Publications were selected from the databases PubMed, Clinical Key Elsevier, Cochrane Library, eBook Business Collection, and Google Scholar, focusing on sterilization methods for decellularized matrix scaffolds. The literature search used keywords such as tissue engineering, decellularization, extracellular matrix, sterilization, gamma sterilization, and acellular transplant. Results. The transplantation of synthetic scaffolds into the human body triggers an immune response to foreign materials. Ideal sterilization or disinfection for decellularized extracellular matrix should effectively eliminate microorganisms while ensuring the sterilized material is non-toxic and preserves physical and chemical properties, as well as biological activity of the biomaterial. Radiation sterilization primarily involves gamma irradiation from Cobalt-60 isotopes and electron beams generated by electron accelerators. In addition to sterilization, decellularized tissue constructs require long-term preservation methods, including cryopreservation, lyophilization, and the use of antibiotics and antifungals stored at –20 °C to –80 °C. Conclusions. Decellularized tissue is receiving significant attention as a potential biological scaffold, as it retains the structure and functions of the extracellular matrix. The application of sterilization methods, such as gamma irradiation from Cobalt-60, ensures deep penetration and preservation of physical properties of the materials.